2005
DOI: 10.1353/dem.2005.0025
|View full text |Cite
|
Sign up to set email alerts
|

Migration and spatial assimilation among u.s. latinos: Classical versus segmented trajectories

Abstract: We used merged data from the Latino National Political Survey, the Panel Study of Income Dynamics, and the U.S. census to examine patterns and determinants of interneighborhood residential mobility between 1990 and 1995 for 2,074 U.S. residents of Mexican, Puerto Rican, and Cuban ethnicity. In several respects, our findings confirm the central tenets of spatial assimilation theory: Latino residential mobility into neighborhoods that are inhabited by greater percentages of non-Hispanic whites (i.e., Anglos) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
177
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(184 citation statements)
references
References 52 publications
5
177
0
2
Order By: Relevance
“…Given that third-and later-generation Mexican-origin families are more likely to disperse into majority Anglo neighborhoods than Puerto Ricans or Cubans (South et al 2005), generation status may be a stronger indicator for community-level influences on the association in education among those of Mexican origin.…”
Section: Resultsmentioning
confidence: 99%
“…Given that third-and later-generation Mexican-origin families are more likely to disperse into majority Anglo neighborhoods than Puerto Ricans or Cubans (South et al 2005), generation status may be a stronger indicator for community-level influences on the association in education among those of Mexican origin.…”
Section: Resultsmentioning
confidence: 99%
“…The general idea is that living in a deprived district can have negative consequences for the social position and social mobility of the residents, because they lack contacts with relevant people and institutions or they have too many "wrong" contacts Massey and Fong, 1990;South and Crowder, 1998;South, Crowder and Chavez, 2005). These negative consequences are mainly problematic for people who are not in a position to move away from disadvantageous neighbourhoods.…”
Section: Introductionmentioning
confidence: 99%
“…In testing aspects of Immigrant Spatial Assimilation Theory, research has generally confirmed the theoretical expectation that residence outside an ethnic concentration is related to increased socioeconomic status, a finding that seems to characterize most Canadian as well as United States places (Allen and Turner, 1996;Alba and Nee, 1999;Alba et al, 2000;Logan et al, 2002;Myles and Hou, 2004;South et al, 2005;Wright et al, 2005;Clark, 2006;Walks and Bourne, 2006). In other words, members of ethnic groups living outside ethnic concentrations tend to have greater educational attainment, better jobs, and/or higher incomes than members of the same groups living within ethnic concentrations.…”
Section: Association Between Residential Concentration and Low Levelsmentioning
confidence: 82%